Simulation‐supported characterization of 3D‐printed biodegradable structures. Issue 4 (15th November 2021) - Schirmer, Richard Wolfgang; Abendroth, Martin; Roth, Stephan; Kühnel, Lisa; Zeidler, Henning; Kiefer, Bjoern
Abstract: In this article, a proof‐of‐concept study is presented, in which in‐situ full‐field deformation measurements via digital image correlation, finite element analysis, and nonlinear optimization techniques are combined to characterize the heterogeneous structural behavior of a bio‐based material 3D‐printed via binder jetting. The special features of this composite material are its biodegradability and its easy manufacturability using conventional 3D printers. The binder‐jetting process enables innovative applications such as additively manufactured, highly customized, recyclable, or compostable packaging solutions. Compared to other 3D printing techniques, it is relatively fast and inexpensive and can make use of raw material powders that are by‐products of the food or other industries. As an initial step towards gaining a simulation‐supported understanding of the complex process‐structure‐property relations, a first quantitative assessment of the effective behavior of a bio‐based binder‐jetted material is conducted under the following operating assumptions: (i) Its mechanical response can be described by means of a nonlinear elasto‐plastic constitutive law, enriched by a cohesive damage model capturing failure on the structural level, (ii) established mechanical tests on a 3D‐printed component, involving standardized sample geometries, and optical measurements, should yield sufficient information to allow the identification of the corresponding material parameters. First, experimental results of optically monitored four‐point bending tests, with varying alignments of loading axes and printing directions, are presented in detail. Then the proposed parameter identification strategy is explained and its capabilities and limitations, as made evident from quantitative case studies based on the measured structural response data, are thoroughly discussed.